Mitochondrial Homeostasis–Related lncRNAs are Potential Biomarkers for Predicting Prognosis and Immune Response in Lung Adenocarcinoma - Peng, Bo; Lou, Han; Chen, Chen; Wang, Lei; Li, Huawei; Lu, Tong; Na, Ruisi; Xu, Ran; Xin, Tong; Yao, Lingqi; Xu, Henghui; Wang, Kaiyu; et al. (Frontiers in Genetics, 2022)
The prognosis of the most common histological subtype of lung cancer, lung adenocarcinoma (LUAD), is relatively poor. Mitochondrial homeostasis depends to a great extent on coordination between mitophagy and mitochondrial biogenesis, the deregulation of which is causative in various human diseases, including cancer. There is accumulating evidence that long non-coding RNAs (lncRNAs) are critical in predicting prognosis and immune response in carcinoma. Therefore, it is critical to discern lncRNAs related to mitochondrial homeostasis in LUAD patients. In this study, we identified mitochondrial homeostasis-related lncRNAs (MHRlncRNAs) by co-expression analysis. In order to construct a prognostic signature composed of three MHRlncRNAs, univariate and multivariate Cox regression analyses were performed. Kaplan-Meier analysis, stratification analysis, principal component analysis (PCA), receiver operating characteristic (ROC) curve, gene set enrichment analysis (GSEA) and nomogram were applied to evaluate and optimize the risk model. Subsequently, we identified the mitochondrial homeostasis-related lncRNA signature (MHLncSig) as an independent predictive factor of prognosis. Based on the LUAD subtypes regrouped by this risk model, we further investigated the underlying tumor microenvironment, tumor mutation burden and immune landscape behind different risk groups. Likewise, individualized immunotherapeutic strategies and candidate compounds were screened to aim at different risk subtypes of LUAD patients. Finally, we validated the expression trends of lncRNAs included in the risk model by quantitative real-time polymerase chain reaction (qRT-PCR) assays. The established MHLncSig may be a promising tool for predicting prognosis and guiding individualized treatment in LUAD.